2016
DOI: 10.1002/eat.22562
|View full text |Cite
|
Sign up to set email alerts
|

The body project 4 all: A pilot randomized controlled trial of a mixed‐gender dissonance‐based body image program

Abstract: Objective The Body Project is a cognitive dissonance-based body image improvement program with ample research support among female samples. More recently, researchers have highlighted the extent of male body dissatisfaction and disordered eating behaviors; however, boys/men have not been included in the majority of body image improvement programs. This study aims to explore the efficacy of a mixed-gender Body Project compared to the historically female-only body image intervention program. Method Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
2
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 36 publications
7
78
2
4
Order By: Relevance
“…We observed clinically meaningful reductions in ED risk factors and bulimic symptoms, consistent with previous work in college‐aged men and women (Becker et al, ; Brown & Keel, ; Kilpela et al, ; Stice et al, ). Effect sizes for the present study were comparable to those in the Body Project 4 All (Kilpela et al, ); of note, our study produced slightly lower effects for muscularity and body fat dissatisfaction (current study: d = .44–.66; Kilpela et al, : d = .55–.79), and slightly higher effects for the EDE‐Q (current study: d = .76–1.16; Kilpela et al, : d = .31–.62). Effect sizes for the current study were somewhat smaller than our intervention adapted for sexual minority men (Brown & Keel, ); potentially, our prior trial was more successful in establishing a sense of community and addressing concerns specific to sexual minority men than the current trial in men more broadly.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed clinically meaningful reductions in ED risk factors and bulimic symptoms, consistent with previous work in college‐aged men and women (Becker et al, ; Brown & Keel, ; Kilpela et al, ; Stice et al, ). Effect sizes for the present study were comparable to those in the Body Project 4 All (Kilpela et al, ); of note, our study produced slightly lower effects for muscularity and body fat dissatisfaction (current study: d = .44–.66; Kilpela et al, : d = .55–.79), and slightly higher effects for the EDE‐Q (current study: d = .76–1.16; Kilpela et al, : d = .31–.62). Effect sizes for the current study were somewhat smaller than our intervention adapted for sexual minority men (Brown & Keel, ); potentially, our prior trial was more successful in establishing a sense of community and addressing concerns specific to sexual minority men than the current trial in men more broadly.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, only one recently published study has examined TBP for men, regardless of sexual orientation. The Body Project 4 All (Kilpela et al, ), a mixed‐gender version of TBP, found significant improvements in body fat, muscle, and overall body dissatisfaction for men compared with waitlist control at postintervention, with effects largely maintained at 2‐ and 6‐month follow‐up. The authors did not find significant differences for body‐ideal internalization or overall eating pathology.…”
Section: Introductionmentioning
confidence: 99%
“…This conflicting behavior increases dissonance or discomfort, which in theory helps reduce body ideal internalization and ED risk factors. Kilpela and colleagues [49] developed a mixed-gender dissonance-based program that demonstrated efficacy at reducing body dissatisfaction in multiple domains (i.e., body fat, muscularity, and overall) for male college students compared to waitlist control, with effects maintained through 6-month follow-up. Brown and colleagues [50] examined the efficacy of a dissonance-based intervention targeting traditional ED and muscle dysmorphia-related psychopathology and demonstrated greater improvements in body-ideal internalization, dietary restraint, bulimic symptoms, drive for muscularity, and muscle dysmorphia symptoms compared to waitlist post intervention and at 1-month follow-up.…”
Section: Prevention and Treatment Of Traditional And Muscularity-oriementioning
confidence: 99%
“…Our sample was more clinically severe and had greater diversity of sexual orientations than prior samples receiving related interventions (Becker et al, 2006;Kilpela et al, 2016;Stice et al, 2012). Our sample was more clinically severe and had greater diversity of sexual orientations than prior samples receiving related interventions (Becker et al, 2006;Kilpela et al, 2016;Stice et al, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…Similar to The Body Project (Becker, Smith, & Ciao, 2006;Stice et al, 2012), our intervention elicited and challenged body ideals through a series of exercises that create cognitive dissonance and erode internalization of unhealthy ideals. The intervention included six modules comprising on-line and off-line activities (see Stice et al, 2012 andKilpela et al, 2016 for more details). The intervention included six modules comprising on-line and off-line activities (see Stice et al, 2012 andKilpela et al, 2016 for more details).…”
Section: Dissonance-based Intervention Conditionmentioning
confidence: 99%